2008
DOI: 10.1063/1.3039806
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and evaluation of the interfacial thermal resistance between a metal and a dielectric

Abstract: Atomic diffusion bonding of wafers with thin nanocrystalline metal films J. Vac. Sci. Technol. B 28, 706 (2010); 10.1116/1.3437515 Thermal conductivity measurement and interface thermal resistance estimation using Si O 2 thin film Rev. Sci. Instrum. 79, 054902 (2008); 10.1063/1.2927253Thermal wave studies of thin metal films and structures AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
(12 reference statements)
2
26
0
Order By: Relevance
“…The discrepancy (an order of magnitude) between our measurement and their computational prediction could arise from (i) the theory based on DMM tends to underestimate Interfacial Thermal Resistance unless the temperature is very low and (ii) less than perfect atomic structure of the interface in this study. Chien et al [29] studied the interfaces between metal and dielectric and reported the thermal boundary resistance of 3.54 Â 10 À8 m 2 K/W for the Al-SiO 2 interface, which is about 50% of value obtained by our technique. A reason for such discrepancy could be due to larger surface roughness or possible contamination at the interfaces in this study, where the SiO 2 layer undergoes reactive ion etching before the metallization at selected areas using a shadow mask.…”
Section: Resultsmentioning
confidence: 44%
“…The discrepancy (an order of magnitude) between our measurement and their computational prediction could arise from (i) the theory based on DMM tends to underestimate Interfacial Thermal Resistance unless the temperature is very low and (ii) less than perfect atomic structure of the interface in this study. Chien et al [29] studied the interfaces between metal and dielectric and reported the thermal boundary resistance of 3.54 Â 10 À8 m 2 K/W for the Al-SiO 2 interface, which is about 50% of value obtained by our technique. A reason for such discrepancy could be due to larger surface roughness or possible contamination at the interfaces in this study, where the SiO 2 layer undergoes reactive ion etching before the metallization at selected areas using a shadow mask.…”
Section: Resultsmentioning
confidence: 44%
“…12) As a result, our numerical predictions show good agreement with the experimental data and previous results. 24) Even when previous researchers assumed that the interface layer was very thin, 18) they were unable to suggest a suitable thickness and their estimations were on the order of a few nanometers. 18,29,36) In the present study we created an interfacial region between the Au film and SiO 2 substrate for convenient modeling of a metal-nonmetal interface region, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is valid under our conditions of laser irradiation in which electrons in the valance band of SiO 2 are not excited beyond a band gap energy of 9.0 eV for SiO 2 . 18,[26][27][28] Therefore, the energy transport via electrons can be neglected in a SiO 2 layer where conductive heat transfer becomes dominant. We used the simple conduction equation for a dielectric SiO 2 layer:…”
Section: Numerical Modeling and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations